A Quantitative Analysis of a Probiotic Storage Media for Avulsed Teeth - KARGÜL, BETÜL; PEKER, MEHMET SERTAÇ; YILMAZ, MÜESSER AHU (UNIV ZAGREB, SCH DENTAL MEDICINE, 2015)
Aim: The aim of the present in vitro study was to investigate the potential of a storage medium, probiotic yogurt (Bifidibacterium animalis DN 173010) in comparison with Hank's balanced salt solution (HBSS), saline and milk in maintaining viable periodontal ligament (PDL) cells on simulated avulsed teeth. Materials and methods: Thirty-six freshly extracted single-rooted human teeth with closed apices were divided into six experimental groups (N=6). The teeth were extracted as atraumatically as possible and washed in sterile saline solution to eliminate residual blood. Following extractions, the coronal 3 mm of PDL tissues were scraped with a #15 scalpel to remove cells that may have been damaged. The positive and negative controls corresponded to 0 minutes and an 8-hour dry time, respectively. After extraction, the positive control teeth were immediately treated with dispase and collagenase. The negative control teeth were bench-dried for 8 h, with no follow-up storage solution time, and then placed in the dispase and collagenase. The number of viable protective least significant difference PDL cells were counted under a light microscope with a hemocytometer at 20x magnification and analyzed. Statistical analysis of the data was accomplished using Nonparametric ANOVA complemented by Kruskal-Wallis Test and Dunn's Multiple Comparisons Test. Results: Positive control was found to be significantly better than the others, there were statistically significant differences between positive control and other test groups (p=0.000). The teeth stored in positive control demonstrated the highest number of viable PDL cells followed in order by probiotic yogurt, HBSS, saline and milk. Conclusion: Bifidibacterium animalis DN 173010 seems to be an alternative for the temporary storage of avulsed teeth, due to high number of viable PDL cells. Probiotics may be suitable transport media for avulsed teeth, but further research is warranted using the commercially available products.
Keywords: Tooth Avulsion; Tissue Preservation; Periodontal Ligament; Milk; Hanks Balanced Salt Solution; Saliva; Probiotics